2016
DOI: 10.1128/jvi.00685-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Conserved E2 Residue W420 in Receptor Binding and Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV) enters cells via interactions with several host factors, a key one being that between the viral E2 envelope glycoprotein and the CD81 receptor. We previously identified E2 tryptophan residue 420 (W420) as an essential CD81-binding residue. However, the importance of W420 in the context of the native virion is unknown, as those previous studies predate the infectious HCV cell culture (cell culture-derived HCV [HCVcc]) system. Here, we introduced four separate mutations (F, Y, A, or R) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…However, at lower, physiological, temperatures the intrinsic fluorescence ratio of I438V A524T and ΔHVR-1 E2 were higher than WT (Figure S10A & 4E), consistent with mutant and ΔHVR-1 E2 being biophysically distinct from WT. Notably, HVR-1 is directly upstream of a highly conserved tryptophan residue in AS412 that has been previously demonstrated to be important for CD81 binding (W420, (Cowton et al, 2016; Owsianka et al, 2006)).…”
Section: Resultsmentioning
confidence: 99%
“…However, at lower, physiological, temperatures the intrinsic fluorescence ratio of I438V A524T and ΔHVR-1 E2 were higher than WT (Figure S10A & 4E), consistent with mutant and ΔHVR-1 E2 being biophysically distinct from WT. Notably, HVR-1 is directly upstream of a highly conserved tryptophan residue in AS412 that has been previously demonstrated to be important for CD81 binding (W420, (Cowton et al, 2016; Owsianka et al, 2006)).…”
Section: Resultsmentioning
confidence: 99%
“…Certain residues seem to be key target residues as they are recognized by several bNAbs from different sources these include; W420 in Epitope 1 and F442 in Epitope 2 that are targeted by 12 and 11 bNAbs, respectively (Figure 2 ). We have shown that W420 is a critical residue modulating interactions with the cellular receptors CD81 and SR-BI ( 31 ). Other residues only form part of the epitope for 1 bNAb, for instance, T416, A439, and D533.…”
Section: Resultsmentioning
confidence: 99%
“…Luciferase-expressing MLV pseudoparticles containing the E1 and E2 glycoproteins from JFH1 HCV strain were generated as described [ 68 ] along with their corresponding JFH1 E1-E2 deficient controls (particles generated only with MLV core) and used to challenge IFNλ-stimulated Huh7 cells. Huh7 cells grown in 96-well plates overnight (seeded at 4 x 10 3 cells per well) were stimulated with IFNλs for 24 hrs and transduced with HCVpp.…”
Section: Methodsmentioning
confidence: 99%